Menggerakkan Pemanfaatan Tanaman Obat Keluarga di Desa Nglanggeran, Kecamatan Patuk, Kabupaten Gunung Kidul, D.I. Yogyakarta - Aris Widayati; Yosef Wijoyo; Putu Dyana Christasani; Titien Siwi Hartayu; Erna Tri Wulandari (Jurnal Pelayanan dan Pengabdian Masyarakat (Pamas), 2023)
A Community Service Program (PkM / Pengabdian kepada Masyarakat) have been carried out named “The Utilization of Family Medicinal Plants (TOGA / Tanaman Obat Keluarga) among Mothers in Nglanggeran Village, Patuk District, Gunung Kidul Regency, D.I. Yogyakarta”. This PkM activity aims to provide information to the Women Farmers Group (KWT / Kelompok Wanita Tani) in Nglanggeran Village about the benefits of family medicinal plants that can be planted around the house. This activity was carried out in May 2022. Education was carried out using the modified CBIA (Active Person Learning Method). The CBIA method facilitates participants to be active in learning the material through small group discussions led by a facilitator. The results of group discussions are written in working papers and presented to the plenary among groups. The results showed that: 1) participants still considered the use of herbs to have no side effects at all; 2) they are used to using popular medicinal plants to treat minor health complaints, such as crushed dadap leaves to treat fever, squeezed turmeric water for stomach pain, lime juice and soy sauce for cough medicine, and bay leaf decoction for gout. The mothers' response to holding this event was very enthusiastic, so it was necessary to carry out further activities in the form of training on TOGA processing to maintain family health.